Discordant Clinical Course of Vitamin-D-Hydroxylase (CYP24A1) Associated Hypercalcemia in Two Adult Brothers With Nephrocalcinosis - Tilman Jobst-Schwan; Andrea Pannes; Karl Peter Schlingmann; Kai-Uwe Eckardt; Bodo B. Beck; Michael S. Wiesener (Karger Publishers, 2015)
Background/Aims: Hypercalcemia can result in nephrocalcinosis/nephrolithiasis and may lead to renal failure. Idiopathic infantile hypercalcemia is caused by mutations of the CYP24A1 gene, which regulates vitamin D activity. Classically infants present with hypercalcemia. Recently, a number of individuals have been reported with late onset clinical manifestation or late diagnosis in adulthood. All these patients are believed to show hypercalciuria. Methods: We report a 24 year old patient of healthy consanguine parents. Genetic analysis was performed by Sanger sequencing of the CYP24A1 gene in the index patient and targeted exon 2 analysis of all other family members. Results: The patient was hospitalized with severe malaise during an acute EBV-infection. He showed hypercalcemia > 3mmol/l and acute, hypovolemic renal failure with profound nephrocalcinosis, but no hypercalciuria. Genetic workup revealed a homozygous loss-of-function mutation p.E143del in the CYP24A1 gene. His clinically asymptomatic brother showed nephrocalcinosis of lesser degree. Repeatedly, low parathyroid hormone levels were detected in both brothers. Conclusion: This family displays the highly variable phenotype of CYP24A1 biallelic mutation carriers. CYP24A1 associated disease is an important differential diagnosis for the workup and counseling of infants as well as adults with hypercalcemia since a proper genetic diagnosis may result in therapeutic consequences.